2019
DOI: 10.1136/gutjnl-2019-319616
|View full text |Cite
|
Sign up to set email alerts
|

USP22 promotes hypoxia-induced hepatocellular carcinoma stemness by a HIF1α/USP22 positive feedback loop upon TP53 inactivation

Abstract: ObjectiveWe aimed to elucidate the mutual regulation mechanism of ubiquitin-specific protease 22 (USP22) and hypoxia inducible factor-1α (HIF1α), and the mechanism they promote the stemness of hepatocellular carcinoma (HCC) cells under hypoxic conditions.DesignCell counting, migration, self-renewal ability, chemoresistance and expression of stemness genes were established to detect the stemness of HCC cells. Immunoprecipitation, ubiquitination assay and chromatin immunoprecipitation assay were used to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 42 publications
(51 reference statements)
3
121
1
Order By: Relevance
“…The formation of the feedback loop was essential in cancer progression 19 , 54 . Meanwhile, the involvement of Myc has been indicated in certain positive or negative feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the feedback loop was essential in cancer progression 19 , 54 . Meanwhile, the involvement of Myc has been indicated in certain positive or negative feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…Due to uncontrolled growth of HCC leading to intratumor hypoxia, HCC cells are developed with the capacity of more stemness, chemoresistance, and invasive 9,10 . The interactions between hypoxic microenvironment and HCC cells are considered as a key factor causing sorafenib chemotherapy failure 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia leads to HIF-1a stabilization and rapid protein accumulation and increased transcriptional activity (5). Through transcription of several hundred of target genes, HIF-1a is profoundly implicated in many malignant phenotypes, such as angiogenesis, metabolic reprogramming, stemness maintenance, cell survival and proliferation, tumor motility and invasion, immune evasion, and resistance to chemoresistance (6)(7)(8)(9). Recent preclinical studies showed that the combination of cytotoxic chemotherapy with drugs that targeting hypoxia-inducible factors may improve the clinical outcome for TNBC patients (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%